Electoral System and Political Representation in Peru today - García Belaunde, Domingo (1987)
The text analyzes the electoral system and political representation in Peru, highlighting the democratic transition initiated in 1980 after a period of military rule. It is emphasized that the 1979 Constitution strengthened the Executive Branch, established a bicameral system and promoted decentralization through the creation of local governments. Likewise, with respect to the electoral field, it highlights the adoption of the single ballot paper, the “cifra repartidora” and the scrutiny at the polling station, implemented since 1963, which contributed to minimize electoral fraud and to guarantee more transparent processes. The text also recognizes that the National Jury of Elections is the highest authority in electoral matters, with functional autonomy and administrative and jurisdictional competences. Next, in terms of political participation, it examines an increase in representation since 1978, evidenced by the strengthening of political forces such as APRA and Izquierda Unida. Finally, the author emphasizes that, although the system guarantees reliable elections, participation is limited to suffrage, excluding mechanisms such as popular initiative, referendum or plebiscite.